Method of producing thermo sorption split graffiti - Бурдюженко, Л.В. (Proceedings of National Aviation University (archive), 2006)
New way of sorption thermal spliffing graphite creation is represented. Offered technology is recommended for sorbent manufacturing, which could absorb not only oil products but also organic substances.